Effective community mobilization: evidence from Mali - Alzúa, María Laura (2025)
Experts argue that the adoption of healthy sanitation practices, such as hand washing and latrine use, requires focusing on the entire community rather than individual behaviors. According to this view, one limiting factor in ending open defecation lies in the capacity of the community to collectively act toward this goal. Each member of a community bears the private cost of contributing by washing hands and using latrines, but the benefits through better health outcomes depend on whether other community members also opt out of open defecation. We rely on a community-based intervention carried out in Mali as an illustrative example (Community-Led Total Sanitation or CLTS). Using a series of experiments conducted in 121 villages and designed to measure the willingness of community members to contribute to a local public good, we investigate the process of participation in a collective action problem setting. Our focus is on two types of activities: (1) gathering of community members to encourage public discussion of the collective action problem, and (2) facilitation by a community champion of the adoption of individual actions to attain the socially preferred outcome. In games, communication helps raise public good provision, and both open discussion and facilitated ones have the same impact. When a community member facilitates a discussion after an open discussion session, public good contributions increase, but there are no gains from opening up the discussion after a facilitated session. Community members who choose to contribute in the no-communication treatment are not better facilitators than those who choose not to contribute.